(untitled) (Research, Society and Development, 2021)
This study aimed to analyze how situational constraints (lifter distance to attackers and blockers) influenced a volleyball setter’s distribution after reception that allow an organized attack with all attack options and the relationship between the attack tempo and the effect of the attack according to the setting location. The sample comprised 22 games in the 2018 Men’s Volleyball World Championship. The results showed that there was a difference in the distribution while considering the distance between the setter and the striker in position 4 [χ2 (4) = 28.657; p <0.001], the striker in position 6 [χ2 (4) = 23.828; p <0.001], the blocker in position 4 [χ2 (4) = 16.566; p = 0.002] and there was an effect of the attack tempo on the effect of attacks performed by position 6 [χ2 (3) = 15.438; p = 0.001]. From these findings, it is clear that the setter’s decision-making is related to the ecological dynamics of the game and to situational constraints, with the availability of attackers influencing the setter’s distribution and setting, along with the layout of the adversary’s blocking system.